Pragmatic implications of embedded librarianship in academics: a review of eminent literatures. Issue 2 (4th December 2018) - Pati, Bharati; Majhi, Sabitri
Abstract : Purpose: As the concept of "embedded librarianship" is gaining acceptance globally, and a surplus amount of literature is available for the aspiring practitioners, it would be supplementary to carry out such a literature review and bring alike and crucial works together within one piece of writing. This paper aims to gather realistic instances in LIS literature, where embedded librarianship has been practiced successfully. Design/methodology/approach: While the focus of this review paper is on embedded librarians in curricular contexts, the phrase embedded librarian has a variety of meanings, including librarian involvement and integration at the macro levels such as college, department, programme, research team and micro levels such as course designing, semester assignments and competitive preparation etc. List of relevant literatures was collected from Scopus and LISTA database. Later, full text of the listed document was retrieved from different sources. But the literature that included practical role of an embedded librarian was prioritised and the one which incorporated proposed theories was excluded, and hence, 67 of them were found to be fitted for reviewing purpose in the current case. Findings: While planning for any extensional service besides the usual housekeeping ones, a vigorous transformation in the attitude has to be engulfed. Though the conception of embedded librarianship as a whole is an extended version of service deliverance, it can be alienated into sections according to the contextual outline and areas of embedding such as in the research context, pedagogical participation and offering information literacy. Research limitations/implications: This paper provides a panoramic view on the emerging notion of this extended version of librarianship. By successfully practicing the embedded librarianship model, the user group would be benefited and the professionals could justify the ethics of their professionalism. Embedded librarianship in the university context can be a very important endeavour for the future challenges. The proactive initiatives of the librarian along with a handy support from authorities might ensure continuous and effective partnerships. Originality/value: This paper is expected to be one of the initial and review articles in the area of embedded librarianship in academics. It is a highly informative paper on embedded librarianship and will be most useful for researchers to refer this paper for individual study and also will promote the academic librarians for taking initiative to work as effective embedded librarians.